IT governance : a pocket guide - Calder, Alan, 1957- (IT Governance Pub., 2007)
This new downloadable pocket guide in the Practical IT Governance series, is designed to provide the reader with a basic understanding of how an organization's Information Technology supports and enables the achievement of its strategies and objectives.
Keywords: Information technology -- Management.; Technologie de l'information -- Gestion.; BUSINESS & ECONOMICS -- Corporate Governance.; BUSINESS & ECONOMICS -- Leadership.; BUSINESS & ECONOMICS -- Organizational Development.; BUSINESS & ECONOMICS -- Workplace Culture.; Information technology -- Management; IT governance framework.; IT governance.; calder-moir framework.; calder-moir.